A Spectroscopic Study on Nitrogen Electrooxidation to Nitrate. Issue 19 (29th March 2023) - Li, Tieliang; Han, Shuhe; Wang, Yuting; Zhou, Jin; Zhang, Bin; Yu, Yifu
Abstract: As a potential substitute technique for conventional nitrate production, electrocatalytic nitrogen oxidation reaction (NOR) is gaining more and more attention. But, the pathway of this reaction is still unknown owing to the lack of understanding on key reaction intermediates. Herein, electrochemical in situ attenuated total reflection surface‐enhanced infrared absorption spectroscopy (ATR‐SEIRAS) and isotope‐labeled online differential electrochemical mass spectrometry (DEMS) are employed to study the NOR mechanism over a Rh catalyst. Based on the detected asymmetric NO2 − bending, NO3 − vibration, N=O stretching, and N−N stretching as well as isotope‐labeled mass signals of N2 O and NO, it can be deduced that the NOR undergoes an associative mechanism (distal approach) and the strong N≡N bond in N2 prefers to break concurrently with the hydroxyl addition in distal N. Abstract : The powerful electrochemical in situ attenuated total reflection surface‐enhanced infrared absorption spectroscopy (ATR‐SEIRAS) and online differential electrochemical mass spectrometry (DEMS) techniques are employed to detect reaction intermediates. Based on the detected intermediates, the associative mechanism with the addition of hydroxyl at distal N (distal mechanism) is deduced for nitrogen oxidation reaction (NOR).